2002
DOI: 10.1002/cncr.10282
|View full text |Cite
|
Sign up to set email alerts
|

Surgical view of the treatment of patients with hepatoblastoma

Abstract: BACKGROUNDSurgical resection is the cornerstone of treatment for patients with hepatoblastoma (HB). The Society of Pediatric Oncology Liver Tumor Study Group launched its first prospective trial (SIOPEL‐1) with the intention to treat all patients with preoperative chemotherapy and delayed surgical resection. The objective of this article was to assess the assumed surgical advantages of primary chemotherapy.METHODSBetween 1990 and 1994, 154 patients age < 16 years with HB were registered on SIOPEL‐1. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…In the International Society of Pediatric Oncology Liver Tumor Study Group (SIOPEL)-1 study, 22 patients had pulmonary metastases at diagnosis and 7 went on to thoracotomy for resection. Four of the seven patients undergoing thoracotomy were long-term survivors 63 . SIOPEL also studied 59 patients with relapsed hepatoblastoma.…”
Section: Hepatoblastomamentioning
confidence: 98%
See 1 more Smart Citation
“…In the International Society of Pediatric Oncology Liver Tumor Study Group (SIOPEL)-1 study, 22 patients had pulmonary metastases at diagnosis and 7 went on to thoracotomy for resection. Four of the seven patients undergoing thoracotomy were long-term survivors 63 . SIOPEL also studied 59 patients with relapsed hepatoblastoma.…”
Section: Hepatoblastomamentioning
confidence: 98%
“…Patients with metastases have a much lower survival rate (25–50%) compared to those without 63, 64 . While early case reports showed the potential for cure following metastasectomy, initial chemotherapy trials also showed the possibility of complete resolution of lung metastases with chemotherapy alone.…”
Section: Hepatoblastomamentioning
confidence: 99%
“…The amount and type of adjuvant chemotherapy vary depending on the risk category. Fortunately, most hepatoblastoma tumors are chemosensitive, and more than 80% of tumors that were previously unresectable do eventually become amenable to surgery after initiation of chemotherapy 6 . In cases of PRETEXT stage I–III in which hepatoblastoma remains in close proximity to essential vascular structures, or in all cases of multifocal PRETEXT IV, liver transplantation becomes the only hope for cure.…”
Section: Hepatoblastoma: Backgroundmentioning
confidence: 99%
“…Tumor histology shows varying mixtures of the more differentiated fetal, less differentiated embryonal cells and undifferentiated small cells (SCU)3. Chemotherapy followed by local resection can be curative45. However, not all tumors are chemosensitive and liver transplantation is needed if the tumor cannot be resected surgically because of size, multifocality or proximity to or invasion of large central vessels6.…”
mentioning
confidence: 99%
“…However, not all tumors are chemosensitive and liver transplantation is needed if the tumor cannot be resected surgically because of size, multifocality or proximity to or invasion of large central vessels6. Survival rates vary from 60–80% and chemotherapy sequelae such as deafness are common among survivors, suggesting room for improvement567. The pathognomonic overexpression of β-catenin in HBL is not prognostic.…”
mentioning
confidence: 99%